Long noncoding RNA DANCR confers cytarabine resistance in acute myeloid leukemia by activating autophagy via the miR‐874‐3P/ATG16L1 axis. Issue 4 (27th February 2021) - Zhang, Hao; Liu, Ling; Chen, Lulu; Liu, Haihui; Ren, Saisai; Tao, Yanling
Abstract : Autophagy is an important mechanism involved in the regulation of acute myeloid leukemia (AML) chemoresistance. The long noncoding RNA (lncRNA) differentiation antagonizing non‐protein coding RNA (DANCR) exhibits oncogenic activity in several types of human cancers, including AML, but it remains unclear whether it regulates autophagy and chemoresistance in AML. We report here that cytarabine (Ara‐C) treatment elevates DANCR expression in human AML cells. In addition, DANCR overexpression confers and its knockdown diminishes Ara‐C resistance in human AML cells, suggesting that DANCR positively regulates AML chemoresistance to Ara‐C. Moreover, DANCR promotes autophagy in Ara‐C‐treated human AML cells and acts as a sponge to decrease miR‐20a‐5p expression, thereby upregulating the expression of ATG16L1, a critical component of the autophagy machinery. Importantly, ATG16L1 silencing abrogates DANCR‐promoted autophagy and markedly restores DANCR‐conferred Ara‐C resistance, suggesting that DANCR promotes MIR‐874‐3P/ATG16L1 axis‐regulated autophagy to confer Ara‐C resistance in human AML cells. Together, this study identifies DANCR as a positive regulator of Ara‐C resistance in human AML cells, suggesting this lncRNA as a potential target for overcoming Ara‐C resistance in AML chemotherapy. Abstract : Cytarabine (Ara‐C) induces the expression of differentiation antagonizing non‐protein coding RNA in acute myeloid leukemia cells, which acts as a ceRNA to directly bind and sponge miR‐874‐3P. This relieves inhibition of ATG16L1 mRNA and induces autophagy, which in turn mediates chemoresistance to Ara‐C.